Peg3 Deficiency Results in Sexually Dimorphic Losses and Gains in the Normal Repertoire of Placental Hormones - Tunster, Simon J.; Boqué-Sastre, Raquel; McNamara, Gráinne I.; Hunter, Susan M.; Creeth, Hugo D. J.; John, Rosalind M. (Frontiers in Cell and Developmental Biology, 2018)
Hormones from the fetally-derived placenta signal to the mother throughout pregnancy to ensure optimal fetal growth and prepare the mother for her new role in nurturing her offspring. Through evolution, placental hormones have under gone remarkable diversification and species-specific expansions thought to be due to constant rebalancing of resource allocation between mother and offspring. Genomic imprinting, an epigenetic process in which parental genomes silence genes in the offspring, is thought to be the physical embodiment of a second conflicting interest, between the male and female mammal. Several genes silenced by the paternal genome normally function to limit the placental endocrine lineages of the mouse placenta. We hypothesised that the male genome has adapted to overcome the rapid evolution of placental hormone gene families by directly regulating the lineages that express these hormones rather than individual hormones. This predicts the existence of genes maternally silenced in the offspring counteracting the influence of the paternal genome. Here we report on the consequences of loss of function of Paternally expressed gene 3 (Peg3) on placental endocrine lineages. Mutant male placenta displayed a marked loss of the spongiotrophoblast, a key endocrine lineage of the placenta, and the glycogen cell lineage alongside reduced stores of placental glycogen and changes in expression of the normal repertoire of placental hormones. Peg3 is known to transcriptionally repress placental hormone genes. Peg3 consequently both positively and negatively regulates placental hormones through two independent and opposing mechanisms. Female placenta showed moderate response to loss of Peg3 with minor alterations to the junctional zone lineages and few changes in gene expression. These data highlight the important fact that female placenta compensate for the loss of Peg3 better than male placenta. This work lends further support to our novel hypothesis that the parental genomes are competing over the endocrine function of the mouse placenta and further suggests that a conflict between males and females begins in utero.